Sleep abnormality in neuromyelitis optica spectrum disorder. Issue 3 (June 2015) - Song, Yijun; Pan, Liping; Fu, Ying; Sun, Na; Li, Yu-Jing; Cai, Hao; Su, Lei; Shen, Yi; Cui, Linyang; Shi, Fu-Dong
Abstract : Objectives: We investigated the sleep structure of patients with neuromyelitis optica spectrum disorder (NMOSD) and the association of abnormalities with brain lesions. Methods: This was a prospective cross-sectional study. Thirty-three patients with NMOSD and 20 matched healthy individuals were enrolled. Demographic and clinical characteristics of patients were collected. Questionnaires were used to assess quality of sleep, daytime sleepiness, fatigue, and depression. Nocturnal polysomnography was performed. Results: Compared with healthy controls, patients with NMOSD had decreases in sleep efficiency (7%; p = 0.0341), non-REM sleep N3 (12%; p < 0.0001), and arousal index (6; p = 0.0138). REM sleep increased by 4% ( p = 0.0423). There were correlations between arousal index and REM% or Epworth Sleepiness Scale ( r = −0.0145; p = 0.0386, respectively). Six patients with NMOSD (18%, 5 without infratentorial lesions and 1 with infratentorial lesions) had a hypopnea index >5, and all of those with sleep apnea had predominantly the peripheral type. The periodic leg movement (PLM) index was higher in patients with NMOSD than in healthy controls (20 vs 2, p = 0.0457). Surprisingly, 77% of the patients with PLM manifested infratentorial lesions. Conclusions: Sleep architecture was markedly disrupted in patients with NMOSD. Surveillance of nocturnal symptoms and adequate symptomatic control are expected to improve the quality of life of patients with NMOSD.